1994
DOI: 10.1164/ajrccm.149.1.8111607
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory responses to repeated prolonged exposure to 0.12 ppm ozone.

Abstract: Repeated exposure to high concentrations of ozone results first in augmentation (typically on the second day) and then attenuation of pulmonary response in humans. To determine the effects of repeated prolonged low-concentration ozone exposure, we exposed 17 healthy nonsmoking male subjects to 0.12 ppm ozone for 6.6 h on 5 consecutive days. Subjects were also exposed once to filtered air. Volunteers exercised at a ventilation of approximately 39 L/min for 50 min of each hour during the exposure. Spirometry, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 0 publications
2
42
1
4
Order By: Relevance
“…Given the relatively complex physiologies surrounding each of these functional and epithelial responses, this suggests that more than a single host factor is likely responsible for modulating susceptibility to O 3 . Individual airway responses to ozone, for example the FEV 1 and/or AHR, have been shown by us and others to be highly repeatable if the subject is restudied under identical exposure conditions (13,14,34). Thus these response elements demonstrate high levels of reproducibility for periods of time that may extend over a period of at least 12 mo.…”
Section: Discussionmentioning
confidence: 81%
“…Given the relatively complex physiologies surrounding each of these functional and epithelial responses, this suggests that more than a single host factor is likely responsible for modulating susceptibility to O 3 . Individual airway responses to ozone, for example the FEV 1 and/or AHR, have been shown by us and others to be highly repeatable if the subject is restudied under identical exposure conditions (13,14,34). Thus these response elements demonstrate high levels of reproducibility for periods of time that may extend over a period of at least 12 mo.…”
Section: Discussionmentioning
confidence: 81%
“…Oxidative stress from O 3 exposure has been shown to induce airway hyperesponsiveness in humans (36,37). These authors have suggested that because of these effects, O 3 exposure is likely to contribute to asthma morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The acute development of airway hyperreactivity may be vagally mediated, and the responsiveness can be reversed with atropine premedication (18,21). Investigations have utilized single-or multiple-exposure plans (9,22); however, assessments of hyperreactivity were not usually conducted at later time points (i.e., 1 day postexposure) when O 3 -induced inflammation of the airways and lung parenchyma have been well characterized (11). In one study of healthy subjects, an O 3 concentration of 200 ppb did not provoke airway responsiveness either immediately or 1 day postexposure (26), although hyperresponsive airways have been reported after exposure to high concentrations (400-600 ppb) of O 3 (18,32).…”
Section: Discussionmentioning
confidence: 99%